2009
DOI: 10.1073/pnas.0902882106
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of proteostasis represents an early molecular event in Caenorhabditis elegans aging

Abstract: Protein damage contributes prominently to cellular aging. To address whether this occurs at a specific period during aging or accumulates gradually, we monitored the biochemical, cellular, and physiological properties of folding sensors expressed in different tissues of C. elegans. We observed the age-dependent misfolding and loss of function of diverse proteins harboring temperature-sensitive missense mutations in all somatic tissues at the permissive condition. This widespread failure in proteostasis occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
604
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 605 publications
(654 citation statements)
references
References 60 publications
(106 reference statements)
34
604
1
3
Order By: Relevance
“…The likelihood of developing diseases of protein dysfunction, such as neurodegenerative disorders, is increased upon aging, due in part to the decline of the HSR during the aging process (Ben‐Zvi, Miller, & Morimoto, 2009; Labbadia & Morimoto, 2015). Activators of the HSR have been suggested as possible therapeutic strategies for diseases of aging (Balch, Morimoto, Dillin, & Kelly, 2008; Calamini & Morimoto, 2012; Neef, Turski, & Thiele, 2010; Westerheide & Morimoto, 2005), but many of the small molecules known to modulate HSF1 activity have cytotoxicity and poor bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…The likelihood of developing diseases of protein dysfunction, such as neurodegenerative disorders, is increased upon aging, due in part to the decline of the HSR during the aging process (Ben‐Zvi, Miller, & Morimoto, 2009; Labbadia & Morimoto, 2015). Activators of the HSR have been suggested as possible therapeutic strategies for diseases of aging (Balch, Morimoto, Dillin, & Kelly, 2008; Calamini & Morimoto, 2012; Neef, Turski, & Thiele, 2010; Westerheide & Morimoto, 2005), but many of the small molecules known to modulate HSF1 activity have cytotoxicity and poor bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Several sensors have been used to report on PN alterations. In C. elegans, temperature sensitive mutants of the muscle proteins, α-paramyosin and α-myosin, which are tissue-specific and can lead to loss-offunction effects, have been used to measure the folding capacity of cells during heat stress and upon expression of mutant Htt protein (Ben-Zvi et al, 2009;Gidalevitz et al, 2006). Also, proteins such as GFP-CL1, which are limited to reporting changes in specific components of the PN have been employed to measure the degradation capacity of cells (Bence et al, 2001;Nonaka and Hasegawa, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, several studies have shown that the inability of cells to mount an adequate stress response against misfolded proteins results in low Hsp70 proteins levels and augments the aging process (Bonelli et al, 1999;Fargnoli et al, 1990;Gutsmann-Conrad et al, 1998). This affect is presumably due to an increase load of misfolded proteins on the proteostasis machinery that directly or indirectly affects the folding of the metastable proteome of a cell, resulting in widespread failure of diverse pathways (Ben-Zvi et al, 2009). …”
Section: Ii46 Proteostasis In Agingmentioning
confidence: 99%
“…A model consisting of two subpopulations was consistent with the observations, where a long-lived sub-population showed a robust heat-shock response and a shorter-lived sub-population had a weaker heat-shock response. Ubiquitin-mediated proteolysis to maintain proteostasis was later shown to play an important role in the long-lived population (Ben-Zvi et al 2009). We have demonstrated heterogeneity much earlier in the lifespan.…”
Section: Discussionmentioning
confidence: 99%